An Adaptive Median Filter for Image Denoising - Chin-Chen Chang; Ju-Yuan Hsiao; Chih-Ping Hsieh (2008 Second International Symposium on Intelligent Information Technology Application : 20-22 December 2008, 2008)
In this paper, a new image-denoising filter that is based on the standard median (SM) filter is proposed. In our method, a threshold and the standard median is used to detect noise and change the original pixel value to a newer that is closer to or the same as the standard median. We also incorporate the center weighted median (CWM) filter in our method. With our experimental results, we have made a comparison among our method, the standard median (SM) filter, the center weighted median (CWM) filter, and the tri-state median (TSM) filter, in which our method proves to be superior.